Residential property price hike and speculation - Haron, Razali; Ibrahim, Khairunisah (2018)
This report provides an analytical overview of the behaviour of property price in Malaysia by examining factors influencing the property prices. It aims to determine whether property prices in Malaysia can be explained by the fundamental factors (macroeconomic and financial) or it is due to other unexplained factors. One of the unexplained factors could perhaps be speculation activities and this study intends to explore this possibility. This investigation on the existence of speculation in property market contributes significantly to the body of knowledge thus fills the gap in the literature of property market, particularly in the Malaysian setting. Several quantitative research methods and time-series econometric analyses are employed to meet the objectives of the study and these include the Dynamic Ordinary Least Square (DOLS), Johansen Cointegration Test, Autoregressive Distributed Lags (ARDL) Long Run Estimation, Vector Error Correction Model (VECM), Vector Autoregressive (VAR) and Augmented Dickey-Fuller (ADF). The findings from this study reveal that, based on the different segments of property prices (aggregate, terraced, detached, semi-detached, high-rise) and different states, most of the factors do have significant relationship with property price. In addition, the cointegration analysis indicates that the property price and its factors are cointegrated for all property market segments across states. This implies the presence of a long run relationship between the property price and its determining factors, despite slow adjustment of property price towards equilibrium in the long run. Slow adjustment denotes a persistent deviation from price equilibrium reflecting inefficiency in the residential property market in Malaysia. Results of the granger-causality test indicate that current property price is influenced only by its own past values, which means today’s property price is influenced by the previous three months property price plus the cost of construction. Furthermore, there is a presence of ripple effect in which the house prices in KL, Negeri Sembilan, Perak, Penang and Melaka have spreading effect on other states in Malaysia and this implies that the residential property market in Malaysia is integrated. This study concludes that the residential property price hike in Malaysia is impacted by fundamental factors and is not speculative in nature.